(3GdCeGdjs - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s ((3MGfhJg GdhQGbjf HGdbGgQI s)
(3ChdgG (B:s
(3hbGd QVj Gddg Yfg eedjkG Ydi YOI eSGFd ef eSGFd GdNdGa aj GdfMh(B: (3dG jLhR ONhd GdaGA aj NHQ Ef s
(3BNQgG (B:s
(3hgh hbhY HYV GdUjZ ehbY HYV aKHJ dPdc Cf ePgH GdCNaT aj Pdc CXgQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdCeGdj Ydi eSGFd eaQbI aj GdfMhs
(3HgG fXGe GdJYbjHIs
(3GfXQ aj GdLRA GdChd ef (B18-20 (3fMhs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs